Acceleration of electroactive anammox (electroammox) start-up by switching acetate pre-acclimated biofilms to electroammox biofilms. (November 2017) - Tang, Jiahuan; Chen, Shanshan; Huang, Lingyan; Zhong, Xiaojuan; Yang, Guiqin; Zhou, Shungui
Highlights: Anammox coupled to solid-phase electrodes is defined as electroammox. Switching acetate-rich media to ammonium-rich media is named as the ACAM mode. ACAM operational mode shortens the start-up time of electroammox BESs. ACAM operational mode accelerated the enrichment of electroammox bacteria. Abstract: In this study, an operational method of switching acetate media to ammonium media after the formation of stable acetate-oxidizing biofilms (ACAM mode), was developed. The results showed that the start-up time was shortened to 48 days in the ACAM mode compared to the AM (always ammonium media) mode (>120 days), and an ammonia removal rate of 82 ± 3% was achieved successfully and sustainably in the ACAM mode during the following long-term operation of more than 2 months. Moreover, the ACAM mode was more efficient in enriching both electroammox bacteria and electricigens with Ignavibacteriaceae, Geobacteraceae and Nitrosomonadaceae as dominant families, which could favour the formation of high-performance electroammox biofilms. Thus, the ACAM mode might promote the widespread implementation of the electroammox process.